The Development of Qualitative Research Instruments to Explore the Role of Chief Financial Officer (CFO) - Manoj Chatpibal; Wornchanok Chaiyasoonthorn; Singha Chaveesuk (My University, 2022)
The purpose of this article is to describe the process of developing qualitative research instruments for semi-structured interviews. The data collection instruments used to obtain detailed information for a study of the role of Chief Financial Officer. In semi-structured interviews, qualitative researchers must exercise caution when using both the interview guide and the researcher-self as instruments, especially when robust findings are the primary goal. The article begins with the creation of an interview guide using the approach proposed by Joungtrakul [1]. The interview guide approach was inspired by Patton's [2] six types of questions: behaviors/experiences, opinions/values, feelings/emotions, knowledge, sensory, and background. Second, the article emphasizes the researcher as an instrument. The article describes how the researcher self-prepared for an interview, focusing on the participants' professions and ethical considerations. Contributing to body knowledge would benefit other researchers as part of the process of developing interview guides and self-preparation for conducting interviews. Practitioners would be able to use the findings to conduct quality interviews with finance and accounting professionals, and a similar approach for interviewing other professionals using the qualitative research method.
Keywords: Business Strategies and Management Research; Organizational Management and Leadership; Methodology and Impact of Social Science Research